The Combined Use of Ultrasound and Fetal Magnetic Resonance Imaging for a Comprehensive Fetal Neurological Assessment in Fetal Congenital Cardiac Defects: Scientific Impact Paper No. 60. (27th March 2019) - Pasupathy, D; Denbow, ML; Rutherford, MA
Plain language summary: Heart problems are common in newborn babies, affecting approximately 5–10 in 1000 babies. Some are more serious than others, but most babies born with heart problems do not have other health issues. Of those babies who have a serious heart problem, almost 1 in 4 will have heart surgery in their first year. In the UK, pregnant women are offered a scan at around 20 weeks to try and spot any heart problems. In most cases there is not a clear reason for the problem, but sometimes other issues, such as genetic conditions, are discovered. In recent years the care given to these babies after they are born has improved their chances of surviving. However, it is recognised that babies born with heart problems have a risk of delays in their learning and development. This may be due to their medical condition, or as a result of surgery and complications after birth. In babies with heart problems, there is a need for more research on ultrasound and magnetic resonance imaging (MRI) to understand how the brain develops and why these babies are more likely to have delays in learning and development. This paper discusses the way ultrasound and MRI are used in assessing the baby's brain. Ultrasound is often used to spot any problems, looking at how the baby's brain develops in pregnancy. Advances in ultrasound technologies have made this easier. MRI is well‐established and safe in pregnancy, and if problems in the brain have been seen on ultrasound, MRI may be used to look at these problems in more detail. While it is not always clear what unusual MRI findings can mean for the baby in the long term, increased understanding may mean parents can be given more information about possible outcomes for the baby and may help to improve the counselling they are offered before their baby's birth.